The Anastatic Theory of Atonement - Roland Elliott (TheoLogica)
I propose and defend a model of the atonement, called “anastatic” because of the central role played by Christ’s resurrection. According to this model, union with Christ is achieved by means of expanding the divine act of resurrection to incorporate sinners, thereby granting them access to a new life free from sin. I provide a biblical defense and a Thomistic explication of the model, and close by considering how it might relate to other atonement models within a broader theory of the atonement.